Identification of mobility indices and assessment of heavy metal contamination in sediments and soils nearby small-scale mining sites within Ambalanga River - Avelino, Christopher Alex L.; Junio, Jessica M.; Resurreccion, Augustus C.; Orozco, Christian R. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The present of small-scale mining activities in Itogon, Benguet has put Ambalanga River in danger of heavy metal contamination. This study aims to identify the mobility indices and assess the heavy metal contaminat ion in sediments and soils within the river. Three samples of sediments and soils per sampling site were taken in order to obtain the heavy metal concentration and determine the physico-chemical properties of the samples. Using ASTM standard procedures for pH, specific gravity and particle-size distribution, and Trace2o metalyser equipment, the samples were characterized and their arsenic and lead concentrations were determined. Also, natural and acidic mobility indices were calculated by dividing the concentration of samples immersed to natural and acidic medium by the concentration ceiling value obtained during assessment. Characterization shows that sediments along Ambalanga River are generally sandy particles, with some of the samples being too acidic. Soils are generally heterogeneous in terms of particle composition. Arsenic concentrations range from 12.32 to 114.17 mg/kg, while lead concentrations range from 11.11 to 812.66 mg/kg. Correlation shows that lead concentration is significantly correlated with pH, and assessment results reveal that most of the sediment samples are highly contaminated based on Canadian, and Australian and New Zealand Standards. Soils however still qualify as samples with low level of contamination. Natural and acidic mobility were quantified and preliminary data shows that under natural and acidic conditions of the river, heavy metals attached to the sediments are prone to being mobile, and being released to the surface water.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Sediments (Geology) -- Heavy metal content